Digital Marketing Transformation And Website Design For Silk Footwear Enterprises: Transformasi Pemasaran Digital Dan Desain Website Untuk Perusahaan Alas Kaki Sutera - Intan Rosiana Prihandayani; Alfina Salsabilla; Novi Indah Pramesta; Sumartik (International Consortium of Education and Culture Research Studies, 2024)
General Background The rapid evolution of technology requires small and medium industries to adopt online strategies for market survival. Specific Background CV. KUPU Sutera, a producer of shoes and accessories, faces significant challenges in reaching broader consumers due to reliance on limited social media platforms. Knowledge Gap The absence of a comprehensive digital platform prevents the optimal utilization of online visibility and detailed product information distribution. Aims This study aims to maximize business potential and brand awareness through strategic user interface planning. Results The creation of a responsive digital platform involved collaborative knowledge-sharing sessions on interface principles and Figma application training with the development team. The resulting prototype provides relevant e-commerce features, supported by recommendations for professional studio visual content. Novelty This research integrates participatory technical training with traditional natural fiber product commercialization to construct a user-centered online identity. Implications Adopting these responsive platforms and integrated media strategies allows traditional manufacturers to navigate digitalization, strengthen market positioning, and expand consumer reach. Highlights: Collaborative Figma software training produced a responsive commercial platform for natural fiber commodities. Comprehensive e-commerce interfaces solve the information distribution limitations previously experienced on social media accounts. Professional visual content generation combined with strategic network integration expands the consumer market reach. Keywords: Digital Marketing, Website Design, Brand Awareness, User Experience, Silk Footwear